Intergenerational Smoothing of New Zealand's Future Fiscal Costs - Ross Guest (New Zealand Government, The Treasury, 2013)
This paper applies an overlapping generations model in order to evaluate the implications of intergenerational smoothing of New Zealand's future fiscal costs. The analysis complements the New Zealand fiscal projections of Bell et al. (2010) and the New Zealand tax smoothing analysis in Davis and Fabling (2002). It allows for feedback effects of the tax rate on labour supply through both intratemporal and intertemporal effects which in turn feed back to fiscal projections via taxation revenue. Under Treasury's sustainable debt projections, which implies convergence to a stable 20% net debt to GDP ratio, generations born prior to 1990 are worse off and those born after 2000 are better off (measured by the impact on their remaining lifetime income). However, the magnitudes of the impact on the remaining lifetime income of all generations are small – no greater that 0.7% under the Medium demographic scenario. Those born around 1960 fare the worst, while those born after 2020 fare the best. The losses to current generations are weighed up against the gains to future generations through the social welfare function. The results show that net social gains are possible provided the gains to future generations are given sufficient weight by a low rate of social time preference and a high rate of aversion to variability in aggregate consumption over time. The parameter values required to generate net social gains are close to the bounds of plausible values. The magnitudes of the net social gains/losses range from minus 90 to plus 94 per capita per year.
Keywords: H31; H32; J18; E21; 330